Air trapping in patients with idiopathic pulmonary fibrosis: a retrospective case—control study - Taehun Kim; Mi-Ae Kim; Seong Hwan Youn; Yongshik Kwon; Hyun Jung Kim; Jae Seok Park; Sun Hyo Park (Scientific Reports)
Abstract Idiopathic pulmonary fibrosis (IPF) is characterised by progressive worsening of lung function. In some cases, IPF is accompanied by air-trapping and emphysema. This study aimed to evaluate air trapping quantified with RV/TLC in patients with IPF. This retrospective study included 122 patients diagnosed with IPF in South Korea between January 2011 and December 2020. Air trapping was defined as RV/TLC ≥ 0.40. Increased RV/TLC was found in 34.4% of all patients. The RV/TLC negatively correlated with lung function (forced expiratory volume in 1 s and functional vital capacity [FVC]) and showed consistent results after 1 year of follow-up. After propensity score matching, FVC and diffusion capacity between the groups showed no statistical difference. No difference in lung function decline was found between the increased and not increased RV/TLC groups. Regarding univariable analysis, the patients in the increased RV/TLC group had a lower risk of all-cause mortality (hazard ratio 1.753, P = 0.034). Using multivariable analysis, age, pirfenidone treatment, and FVC were significant factors for survival but not increased RV/TLC. Increased RV/TLC was related to emphysema and demonstrated a negative relationship with lung function. Although increased RV/TLC might relate to poor clinical outcome, it was not independent prognostic factor for IPF.